Estimation of the planning organ at risk volume for the lenses during radiation therapy for nasal cavity and paranasal sinus cancer. Issue 6 (4th August 2015) - Piotrowski, Tomasz; Ryczkowski, Adam; Adamczyk, Marta; Jodda, Agata
Abstract: Introduction: To establish the optimal planning risk volume (PRV) of the lenses for patients who are receiving radiotherapy to the nasal cavity and paranasal sinus (NCPSC). Methods: Geometrical uncertainties of the lenses were evaluated for a prospective group of patients (G1). Differences between planned and delivered maximum doses to the lenses were evaluated for every fraction. The relationship between dose differences and geometrical uncertainties were analysed to establish an optimal PRV for the lenses. Obtained results were verified in the second group (G2) of patients for whom calculated PRV was applied. Results: Data of 426 observations for 15 patients from G1 were investigated. The systematic and random errors equalled, respectively, 0.6 mm and 2.3 mm in the medio‐lateral direction; 0.8 mm and 1.6 mm in the cranio‐caudal direction; and 0.4 mm and 1.5 mm in the anterio‐posterior direction. The clinical PRV for the lenses was established at 2 mm. Applied margin was evaluated for 10 patients from G2. The dose distribution in the planning target volume (PTV) for G1 and for G2 was comparable ( P  = 0.122), whereas the differences between planned and delivered doses in the lenses were significantly smaller for G2 ( P  = 0.013). Conclusion: The study showed that for radiotherapy of NCPSC, the PRV for the lenses could be defined as 2 mm. This margin does not affect the dose distribution in the PTV and effectively reduces the differences between planned and delivered doses in the lenses.